Children of migrant parents: Migrating together or left behind. (June 2018) - Fang, Yiping; Shi, Zhilei
Abstract: Migrant parents in China are increasingly choosing to bring their children with them to their migration destination from their place of origin. This paper uses a 2016 migrant survey data to examine whether the likelihood of children living in their parents' migration destinations compared to those left in their places of origin has a correlation with parents' household characteristics, employment status and their participation in the social insurance scheme. Over all, older and better educated parents, longer migration history and intra-provincial move all predict higher likelihood of children moving with parents, the same as being the only child and born in destination cities, but not the child's gender. For the purpose of our analysis, children of migrant parents are disaggregated based on their urban or rural hukou status (household registration). Controlling for household characteristics, we find that migrant parents who have lower monthly savings, or who have access to local health insurance, or who do not have employment contracts are more likely to bring their children along if they are rural registered children. Access to pension could predict higher likelihood of children migration. Improving social insurance schemes for rural hukou migrants to make them at par with those for urban hukou migrants can remove discrepancies in the likelihood of their children's migration.